The Effect of Flow Mind Map on Writing Accuracy and Learning Motivation at Islamic Higher Education - Sabarun, Sabarun; Muslimah, Aisyah H.S.; Muhanif, Slamet; Elhawwa, Tazkiyatunnafs (Universitas Negeri Semarang, 2021)
The investigation attempted to explore the influence of flow mind map on writing accuracy and learning motivation at Islamic Higher Education. There were two variables: flow mind map as a predictor variable; writing accuracy and learning motivation as the outcome variables. The study involved L2 participants at higher education in Kalimantan. The participants was 37 students, consisting of two groups: experiment class and control class. A main effect of one way Anova was used to measure an effect of flow mind map on learners’ writing score and learning motivation. The finding revealed that the value of writing accuracy at F (1,36) = 44.861, SS 3591.045, MS= 3591.045, p= 0.000; and the value of learning motivation at F (1,36) = 40.925, SS 2006.600, MS= 2006.600, p= 0.000. The significance value was below 0.050, meaning there was a statistically difference in the mean of using flow mind map on learners’ writing accuracy and learning motivation. It was recommended that language instructor motivate learners during the learning process. Due to the limited number of sample size, the further investigations with broader scope and larger sample size were needed to validate the research findings.